Effects of dietary isoflavone-genistein on hematological and immunological parameters in pre-brood stock beluga, Huso huso - Bahmani, M.; Ghasemi, R.; Yousefi Jourdehi, A. (2016)
This study was carried out with the aim of detecting the dietary effects of isoflavone-genistein on hematological and immunological parameters in beluga, Huso huso in a 12-week feeding period. Five isonitrogenous (45% crude protein) and isoenergetic (19.5 MJ kg^-1) diets were formulated to contain four graded levels of isoflavone-genistein, namely 0, 0.2, 0.4, 0.8 and 1.6 g kg^-1 diet. Fish (initial average weight: 26.1 ± 1.8 kg) were stocked in ponds in groups of 3 and fed the experimental diets in triplicate. At the end of experiment, physiological indicators, including hematological and immunological parameters, such as red blood cell (RBC), white blood cell count (WBC), hematocrit (Ht), hemoglobin (Hb), lymphocyte, neutrophil, eosinophil, monocyte, haematological indices, lysozyme, total immunoglobulin (IgM) and complementary activities were determined. Results suggested that mean corpuscular hemoglobin concentration (MCHC) and values of neutrophil had significant differences between treatments. The activities of serum lysozyme, IgM, C3 and C4 were significantly influenced by the dietary genistein concentrations. Results indicated that genistein had significant effects on some hematological and immunological parameters in beluga.